Color-tunable photoluminescence of Cu-doped Zn–In–Se quantum dots and their electroluminescence properties. Issue 3 (23rd December 2015) - Cao, Sheng; Ji, Wenyu; Zhao, Jialong; Yang, Weiyou; Li, Chengming; Zheng, Jinju
Abstract : Cu-doped Zn–In–Se QDs with color-tunable photoluminescence emissions are synthesized, and the as-fabricated QD-LEDs exhibit a luminous efficiency of 0.97 cd A −1 . Abstract : Recently, Cu-doped ternary chalcogenide quantum dots (QDs) have attracted extensive attention due to their large Stokes shift and tunable photoluminescence (PL) behavior in the visible and near-infrared (NIR) spectral range, and particularly for their remarkably lower toxicity than their Cd-based counterparts. However, there still remain material- and fabrication-related obstacles in realizing high-performance Cu-doped QDs, which limit their promising applications in light-emitting devices and bio-labeling. In the present study, we report the facile synthesis of high-qualified Cu-doped Zn–In–Se QDs via a hot injection approach, using a heterogeneous dispersion of Se in octadecene (ODE) as a "green" Se precursor. With variation of the ratios of Zn to In, the obtained Cu-doped Zn–In–Se QDs exhibited composition-tunable PL emissions over the most visible spectral window ( ca. 565–710 nm) with a PL quantum yield (QY) up to 38% after coating ZnSe shells, which is the highest one ever reported in this system. Furthermore, we report, for the first time, the exploration of QD light-emitting diodes (QD-LEDs) based on the Cu-doped Zn–In–Se QDs as the active layer, which had a maximum luminance of 320 cd m −2 and a luminous efficiency (LE) of 0.97 cd A −1 (at 98 cd m −2 ), suggesting their promising potential for application in optoelectronic devices.